MENINGKATKAN KEPERCAYAAN DIRI MAHASISWA UNTUK BERTANYA DALAM PERKULIAHAN BAHASA INDONESIA MELALUI INKUIRI - Fitra Afrida Amna; Elvina A Saibi (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Indonesian language lecture activities are the most basic activities. Achieving good results of Indonesian language lectures there are factors that affect both from within and outside the individual. In STIKES Syedza Saintika Public Health Students, student lecture activities are required to be active in Indonesian language lectures, asking and responding, but in fact only a few students play an active role in asking questions. One way to overcome is using the inquiry Approach. The purpose of the study provides a solution to overcome the problem of students who are not confident to ask questions in lectures Indonesian. This type of research is classroom action research. The results illustrate that; 1) The inquiry approach can change the way students lectures are lectured from monotonous and boring Indonesian language lectures towards lectures that make students active, creative, innovative and more confident so that the atmosphere of Indonesian language lectures becomes more lively. 2) The inquiry approach can be presented using various methods according to the demands of Indonesian language lecture materials and lecturers are skilled in their presentation. 3) The inquiry approach is proven to increase students' confidence in asking questions so that the results of indonesian language lectures achieved can be obtained as desired. This can be seen from the interaction of students in lectures, where the activeness of students asking questions in cycle II is higher than in cycle I.